The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/cmr.0000000000000048
|View full text |Cite
|
Sign up to set email alerts
|

Melanomas of unknown primary frequently harbor TERT-promoter mutations

Abstract: Commonly, in patients with melanoma metastases of an unknown primary tumor (MUP), an extensive search for the primary tumor is carried out. Recently, highly recurrent telomerase reverse transcriptase (TERT)-promoter mutations were found in malignant melanomas, which may function as driver mutations of skin cancer. The aim of this study was to test the hypothesis that MUP and mucosal melanomas harbor different prevalences of TERT-promoter mutations. Thirty-nine patients with MUP and 53 patients with mucosal mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 8 publications
2
21
0
1
Order By: Relevance
“…Based on our mutational data we have shown that a population of MUP patients have a similar distribution of BRAF/NRAS alterations to the known primary melanoma patients exposed to similar/identical environmental factors (such as UV exposure, but not exclusively), confirming data from other smaller published series 16,18,23,24,28. The incidence of mutations is consistent with those already observed for melanoma originating on skin without chronic sun damage, which is the most common type in Central and Western Europe 29.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on our mutational data we have shown that a population of MUP patients have a similar distribution of BRAF/NRAS alterations to the known primary melanoma patients exposed to similar/identical environmental factors (such as UV exposure, but not exclusively), confirming data from other smaller published series 16,18,23,24,28. The incidence of mutations is consistent with those already observed for melanoma originating on skin without chronic sun damage, which is the most common type in Central and Western Europe 29.…”
Section: Discussionsupporting
confidence: 86%
“…Because the manifestation of melanoma as MUP does not alter BRAF or NRAS mutation frequency compared with melanomas with known primary site, some other genetic/immunological mechanism enhancing regression must be involved 28. Based on previously published data and our clinical data on MUP patients, supported by mutational status of known genes involved in development of melanoma as well as potential targets of new therapies, we conclude that MUP has similar molecular pattern in terms of BRAF / NRAS alterations and clinical behavior to melanoma of known primary site of the same stage (mainly developed in NCSD) and therefore should be managed and treated according to the same guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…No gender differences were found among urothelial carcinomas in this study or in previous investigations. Interestingly, TERT mutation in melanoma showed a male predominance in one study (51% in males versus 21% in females; P = 0.004), although no gender difference was noted in another study (45% in males versus 39% in females; P = 0.26) . Further investigation is warranted to explore the mechanisms and significance of gender differences of TERT mutation.…”
Section: Discussionmentioning
confidence: 90%
“…Horn et al [23] also reported a germline TERT promoter mutation in a kindred with familial cutaneous malignant melanoma. A recently published study by Egberts et al [27] found a low frequency of TERT promoter mutations in mucosal melanoma, but the frequency in SNMM was not specifically reported. No former study has investigated the frequency of TERT promoter mutations in primary SNMM; therefore, the aim of the current study was to evaluate a large cohort for the presence of TERT promoter mutations and coexisting NRAS and BRAF mutations.…”
Section: Introductionmentioning
confidence: 96%